The Musical Idea and the Basic Image in an Atonal Song and Recitation of Arnold Schoenberg - Jack Boss (Gamut: Online Journal of the Music Theory Society of the Mid-Atlantic, 2009)
Schoenberg’s songs and recitations—tonal, atonal, and serial—can be understood by the perceiver as elaborating two kinds of framework, the musical idea and the basic image. The musical idea generally comprises an opposition of elements, an elaboration of that opposition, and an ultimate resolution. The basic image translates a visual image of some kind into a musical shape, which then serves as a starting point for further development. This article shows how the motivic and harmonic structures of two atonal works—Song 11 of Das Buch der hängenden Gärten, Op. 15, and “Nacht” from Pierrot Lunaire, Op. 21—can be heard as growing out of, respectively, a complete idea and a basic image, and how these frameworks and their motivic/harmonic elaborations parallel the structure and meaning of the texts. Since the article’s insights about harmonic elements and relations are presented using the language of pitch-class set theory, the article also demonstrates ways in which Schoenberg’s notions of coherence intersect with conventional models of pitch-class set coherence. This article is part of a special, serialized feature: A Music-Theoretical Matrix: Essays in Honor of Allen Forte (Part I).